Term - Deposit Waqf Linked Isthisna (TDWLI): Proposed Models, Accounting Aspects, and Risk Management Analysis - Yaser Taufik Syamlan; Sakinah Sakinah; Mursalmina Mursalmina; Asfa Asfiah (Economica: Jurnal Ekonomi Islam, 2020)
Abstract: Islamic banking (further referred to as the Bank) faces two significant problems: excessive concentration in Murabaha financing contracts and high cost of funds. These two classic problems directly impact the development of the Bank and give rise to the stigma of a less innovative and unprofitable industry. This research aims to make a new product breakthrough that can help stakeholders overcome the two problems above. Term Deposit Waqf Linked Isthisna (TDWLI) has 4 variants: TDWLI Perpetual Principal, TDWLI Perpetual Principal + Profit Sharing, TDWLI Periodic Principal, TDWLI Periodic Principal, and + Profit Sharing. The TDWLI Periodic Principal is the variant that is most ready to be applied because, in accounting terms, it has been regulated in PSAK 112. In general, this TDWLI product will provide several advantages for banks to reduce the cost of funds (especially in the main variant of Waqf only). It will increase Isthisna financing, referring to OJK data in 2019, only 0.3% of total financing. In terms of accounting treatment, PSAK 112 must be adjusted especially if the Bank will release a Perpetual-based product variant. The main problem with perpetual-based products is the uncommon features. In perpetual, cash waqf cannot be withdrawn or, in other words, eternal. This research recommends that OJK is expected to study this product more deeply to develop healthy and innovative Islamic banking.Abstrak: Perbankan syariah (selanjutnya disebut Bank) saat ini sedang menghadapi 2 masalah besar yaitu konsentrasi berlebihan di akad pembiayaan Murabaha serta tingginya Cost of Fund. Kedua masalah klasik ini berdampak langsung kepada perkembangan Bank dan memunculkan stigma industry yang kurang inovatif dan tidak menguntungkan. Penelitian ini bertujuan untuk membuat terobosan produk baru yang dapat membantu stakeholders dalam mengatasi kedua masalah diatas. Produk Deposito Waqf Linked Isthisna (DWLI) dengan 4 varian nya baik itu DWLI Perpetual Pokok, DWLI Perpetual Pokok + Bagi Hasil, DWLI Periodic Pokok dan DWLI Periodic Pokok + Bagi Hasil. DWLI Periodic Pokok menjadi varian yang paling siap untuk diaplikasikan karena secara akuntansi sudah diatur dalam PSAK 112. Secara umum produk DWLI ini akan memberikan beberapa keuntungan bagi bank dalam rangka menurunkan cost of fund (terutama pada varian Wakaf pokok saja) serta akan menaikkan pembiayaan Isthisna yang merujuk kepada data OJK tahun 2019 hanya 0,3% dari total pembiayaan. Secara perlakuan akuntansi, PSAK 112 harus disesuaikan terutama apabila Bank akan merelaisasikan varian produk berbasis Perpetual. Permasalahan utama dari produk berbasis perpetual adalah ketidak umuman fitur dimana dalam perpetual, Wakaf uang tidak dapat ditarik atau dengan kata lain abadi. Rekomendasi dari penelitian ini adalah OJK diharapkan dapat mengkaji produk ini lebih dalam demi perkembangan perbank syariah yang sehat dan inovatif.Islamic banking (further referred to as the Bank) faces two significant problems: excessive concentration in Murabaha financing contracts and high cost of funds. These two classic problems directly impact the development of the Bank and give rise to the stigma of a less innovative and unprofitable industry. This research aims to make a new product breakthrough that can help stakeholders overcome the two problems above. Term Deposit Waqf Linked Isthisna (TDWLI) has 4 variants: TDWLI Perpetual Principal, TDWLI Perpetual Principal + Profit Sharing, TDWLI Periodic Principal, TDWLI Periodic Principal, and + Profit Sharing. The TDWLI Periodic Principal is the variant that is most ready to be applied because, in accounting terms, it has been regulated in PSAK 112. In general, this TDWLI product will provide several advantages for banks to reduce the cost of funds (especially in the main variant of Waqf only). It will increase Isthisna financing, referring to OJK data in 2019, only 0.3% of total financing. In terms of accounting treatment, PSAK 112 must be adjusted especially if the Bank will release a Perpetual-based product variant. The main problem with perpetual-based products is the uncommon features. In perpetual, cash waqf cannot be withdrawn or, in other words, eternal. This research recommends that OJK is expected to study this product more deeply to develop healthy and innovative Islamic banking